RETRACTED ARTICLE: Hsa_circ_0008360 sponges miR-186-5p to target CCND2 to modulate high glucose-induced vascular endothelial dysfunction. Issue 14 (18th July 2021) - Zhu, Qian-Qian; Pu, Xi-Bin; Chen, Tian-Chi; Qiu, Chen-Yang; Wu, Zi-Heng; Tian, Lu; He, Yang-Yan; Wang, Xiao-Hui; Shang, Tao; Wang, Xun; Xiang, Yi-Lang; Li, Dong-Lin; et al.
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Qian-Qian Zhu, Xi-Bin Pu, Tian-Chi Chen, Chen-Yang Qiu, Zi-Heng Wu, Lu Tian, Yang-Yan He, Xiao-Hui Wang, Tao Shang, Xun Wang, Yi-Lang Xiang, Dong-Lin Li, and Hong-Kun Zhang. Hsa_circ_0008360 sponges miR-186-5p to target CCND2 to modulate high glucose-induced vascular endothelial dysfunction. Cell Cycle. 2021;20(14):1389-1401. doi: 10.1080/15384101.2021.1918877 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to address all the concerns raised. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.